Safety of the elderly in the hospital environment: international scientific production - Santos, Gabriela Martins; Moreira , Maria Adelaide Silva Paredes (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Reducing the risk of unnecessary harm associated with the health care process to an acceptable minimum is configured as patient safety in the hospital environment. Aim: To analyze the international scientific production on the safety of the elderly in the hospital environment. Method: Bibliometric research, performed on the ISI Web of Knowledge/Web of ScienceTM , in the time frame between the years 1995 and 2021, using the descriptors: “patient safety” and elderly* and “hospital environment”, carried out from the export of these data for the HistCiteTM bibliometric analysis software. Results: 172 publication records were found, in 59 different journals, written by 218 authors who have links with 200 institutions, located in 113 countries. In the analysis of counting the number of citations, the h-index value is equal to 36 and the average number of citations per article is 48.25. The articulation between the 15 publications with the highest impact factor on the subject and the 06 International Patient Safety Goals of the World Health Organization, shows that Goal 3 - improve the safety of high-alert medication- was highlighted with 46.6% of the studies. Implications: The analysis of the indicators on the dynamics and evolution of scientific and technological information showed that there is a gap in knowledge on the subject, presented in a broad and diversified way without demonstrating the existence of an articulation between studies, authors and institutions from all over the world. There is a need to build knowledge networks in the area that allow more studies capable of contributing to the improvement of the safety of the elderly in the hospital environment.